Mengenal Pola Kepengasuhan Santri: Kontribusi Terhadap Pembentukan Karakter Di Pondok Pesantren Syaichona Cholil Samarinda - Moh. Anas; Nur Kholik Afandi (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2024)
Islamic boarding schools play a big role in forming students' character through the parenting patterns that are used. The purpose of this study is to investigate the patterns of parenting at Pondok Pesantren Syaichona Cholil Samarinda and how they contribute to the formation of students' character. Dengan menggunakan metode qualitative, penelitian ini mengumpulkan data melalui observation, depth interviews, dan document studies. Hasilnya menunjukkan bahwa religious values, discipline, responsibility, and independence are the parenting pattern in this pesantren, which are constantly used by caregivers and teachers. The parenting pattern at Pondok Pesantren Syaichona Cholil plays a strategic role in supporting the comprehensive character development of students because it encourages students to follow the rules and builds strong characters ready to face challenges in daily life. Diharapkan bahwa artikel ini akan berfungsi sebagai referensi untuk perkembangan pola parenting di lingkungan pendidikan luar pesantren.